2021
DOI: 10.4236/as.2021.125038
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Internet of Things (IoT) System for Measuring Agricultural Runoff Quantity and Quality

Abstract: Runoff is an important component of the water balance of agricultural fields. Accurate measurement or estimation of agricultural runoff is important due to its potential impact on water quantity and quality. Since runoff from agricultural fields is sporadic and is often associated with irrigation and/or intense rainfall events, manually measuring runoff and collecting water samples for water quality analysis during runoff events is inconvenient and impractical. In the fall of 2017, a field site was selected at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The use and construction of large digital changes for the countryside. Zero people think that deep learning technology is very important for remote sensing data processing, especially in the era of remote sensing big data processing [ 14 ]. Deep learning technology will become the most advanced biological remote sensing technology.…”
Section: State Of the Artmentioning
confidence: 99%
“…The use and construction of large digital changes for the countryside. Zero people think that deep learning technology is very important for remote sensing data processing, especially in the era of remote sensing big data processing [ 14 ]. Deep learning technology will become the most advanced biological remote sensing technology.…”
Section: State Of the Artmentioning
confidence: 99%
“…ThingSpeak.com is an IoT analytics platform service that allows users to aggregate, visualize, and analyze live data streams in the Cloud. We selected ThingSpeak.com because we had already used this service for previous applications [42][43][44][45], we were familiar with it, and it offered all the needed features. Other researchers, such as [30,40], also used ThingsSpeak.com.…”
Section: Internet Of Things (Iot) Systemmentioning
confidence: 99%
“…For example, we designed three IoT systems for soil moisture monitoring [42][43][44] to assist growers in making more accurate and timely irrigation scheduling decisions based on real-time sensor data. Similarly, our team developed another IoT system to monitor agricultural runoff and collect water-quality samples from an agricultural field [45]. Therefore, building on our previous experience, this study aimed to create an affordable Internet of Things (IoT) scale system to measure crop ET.…”
Section: Introductionmentioning
confidence: 99%
“…Knowing the runoff before reaching the rivers is essential to predict the results of major rainfall events in advance. Payero et al (2021) used the Internet of Things (IoT) to develop a surface runoff measurement system utilizing H flumes and eTape liquid level sensor, including a water collection system for analyzing the impacts of runoff in soybean and cotton fields with and without coverages and obtained an R 2 = 0.99 with the calibration. Schallner et al (2021) monitored runoff using low-cost UBeTube technology and concluded that the methodology, with proper calibration, could be used in pastures.…”
Section: Introductionmentioning
confidence: 99%